Economic Justice as a Legal Strategy for Countering Terrorism in Nigeria: Learning from the United Kingdom Experience - Paul Atagamen Aidonojie; Obieshi Eregbuonye; Mercy Osemudiame Okpoko; Ismaila Hassan; Micheal Inagbor (Contrarius, 2026)
Nigeria continues to prioritise military intervention as the principal response to terrorism; however, persistent violence indicates that structural socio-economic inequalities, unemployment, and regional marginalisation sustain conditions conducive to radicalisation. In contrast, the United Kingdom integrates economic justice within its legal and policy framework, thereby complementing security measures with socio-economic regulation. This study analyses the role of economic justice as a lawful and sustainable counter-terrorism strategy through a comparative examination of the United Kingdom and Nigeria. This research aims to evaluate the legal basis for implementing economic justice measures in counterterrorism and to assess their relevance for long-term peacebuilding in Nigeria. The study employs a doctrinal research method, systematically examining legislation, public policy instruments, and scholarly works using the PRISMA framework to ensure transparent and rigorous source selection. The findings demonstrate that, first, the United Kingdom establishes a normative and institutional framework that links welfare regulation and social protection to the prevention of violent extremism; second, it enforces financial accountability and regulatory oversight to limit structural grievances and disrupt potential channels of radicalisation; and third, Nigeria maintains a predominantly securitised counter-terrorism regime that lacks enforceable economic rights and targeted development legislation. The study concludes that Nigeria should reform its legal framework by embedding inclusive economic governance, strengthening institutional accountability, and codifying socio-economic rights as integral components of a sustainable counter-terrorism strategy.